Novel Filters Based Operational Scheme for Five-Level Diode-Clamped Inverters in Microgrid - Elnady, A.; Al-Shabi, M.; Adam, Ali Ahmed (Frontiers in Energy Research, 2020)
This paper introduces a new operational scheme for several multilevel (five-level diode-clamped) inverters in the microgrid. The presented operational scheme has a central structure (different from the distributed controllers for droop schemes) to alleviate the drawback of the conventional droop control for microgrid operation. The contribution of this paper is focused on the suggested operational scheme, which has two contributory components. The first component is the novel smooth variable structure filters (SVSF), which are formulated to estimate the disturbances of voltage harmonics and voltage unbalance. The second component is an efficient adaptive sliding mode controller to operate these inverters. This proposed operational achieves equal power sharing among working inverters, compensating for voltage unbalance at the point of common coupling (PCC) at loads, and mitigation for voltage harmonics at the PCC. More importantly, the propounded operational scheme efficiently stabilizes voltage with the variation of balanced, unbalanced, and non-linear loads in addition to the seamless transient and steady-state performance for injected power by inverters. The performance of the suggested operational scheme is justified by simulation results.